Reduction of Leachability of Sewage Sludge by Alum Treatment - Mortula, Maruf (2014)
The sustainable disposal practices of waste materials have drawn much attention in the last two decades. One of the growing disposal practices is the use of land-based application (e.g. fertiliser). However, the application poses concerns of contamination from heavy metals and nutrients. Therefore, there appeared to be a growing necessity for finding appropriate technology to address the concerns related to leaching from sewage sludge. The objective of this paper is to assess the applicability of alum treatment of biologically treated sewage sludge for reduction of leachability. Alum and lime were used for the treatment of sewage sludge. Laboratory-based batch and column tests were conducted to assess the effect of alum treatment on leachability. Batch experimental results indicated that alum treatment was capable of reducing phosphorus and other heavy metal leaching. However, some of the aluminium appeared to have leached into the water. Column experimental results indicated that alum treatment was capable of reducing phosphorus, copper and ammonia leaching from sewage sludge, but indicated an increase in aluminium and chromium leaching. However, the leaching of chromium and copper was at low concentrations, indicating the necessity of further exploration onto sewage sludge from different wastewater treatment plants.